The Labor Market Integration of Migrants: Barcelona, 1930 - Javier Silvestre; María Isabel Ayuda; Vicente Pinilla (European Historical Economics Society (EHES), 2011)
Very few empirical studies have analyzed the labor market performance of internal migrants in the nineteenth and early twentieth centuries. Using a new dataset, this article examines the occupational attainment of migrants, mostly internal migrants, in the city of Barcelona. We find that, in comparison with natives, the occupational outcome of migrants is partly explained by differences in labor market experience and skills. Nevertheless, other factors also appear to play an important role. Estimates, moreover, do not suggest the existence of improved economic assimilation over time. The results indicate that at least some groups of migrants faced barriers to occupational mobility.
Keywords: J24; J61; N34; 330; labor market integration; migrants; occupations; historical labor market